Stopping the Unstoppable: Unconventional Methods to Prevent the Biofilm Growth - Jain, Neha; Mansuri, Abdulkhalik (Current Drug Discovery Technologies, 2020)
Biofilms are consortia of microorganisms encased in extracellular matrix that protect cells from adverse conditions. A biofilm matrix is typically composed of extracellular DNA, cellulose and proteinaceous amyloid fibers. The matrix aids in adhesion to abiotic and biotic surface including medical devices and host tissues. The presence of biofilm makes bacteria more resilient and non-responsive to most current treatment regimes at disposal. Therefore, biofilm-associated infections are serious threat in hospital settings and pose a huge burden on economy. Inhibition of matrix components (cellulose and/or amyloid formation) has emerged as a lucrative alternative strategy to cure biofilm-related infections and combat antibiotic resistance. Here we review the current and emerging therapeutic interventions to mitigate persistent infections due to biofilms. The successful implementation of these interventions will have a huge impact on alleviating the current financial burden on healthcare services.
Keywords: antibiotic resistance